Rural Development NGOs and Service Delivery to the Very Poor: An Empirical Analysis of a Training Center in Rural Cameroon - Azibo, Balgah Roland; Vubo, Emmanuel Yenshu; Mbue, Innocent Ndoh; Kimengsi, Jude Ndzifon (Asian Journal of Agriculture and Rural Development, 2015)
The role of development nongovernmental organizations (DNGOs) in driving change, servicing the very poor and reducing poverty especially in rural areas in developing countries has been generally affirmed in the rural economics literature. This romantic image accounts to a large extent for the exponential numeric growth observed in the sector, and for burgeoning research on the subject by rural development economists. However, not enough empirical evidence exists on the extent to which such organizations actually service the very poor. This paper uses the example of a rural development NGO in the administrative unit of North West Cameroon to assess the extent to which the very poor actually benefit from DNGO services. A relative poverty approach is applied, allowing for the use of individual indicators and computed poverty indices to compare beneficiaries and non-beneficiaries of the DNGO service delivery based on cross sectional data. The results indicate that the DNGO serviced mainly poor communities. However, a disproportionately higher share of the benefits (60%) went to groups that were already well off before service delivery, than to the very poor. The paper then emphasizes the need for DNGOs to carry out poverty analysis prior to service delivery, as a prerequisite to effectively reach out to the very poor, particularly in rural areas in Cameroon.